Effects of plant extracts on patients with heart failure: a network meta-analysis of randomized controlled trials - Deng, Jieyin; Huang, Ye; Fu, Dehui; Deng, Yi; Yu, Ke; Lan, Cong (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceHeart failure (HF) is a major global health challenge. Traditional therapies have limitations, while recent studies highlight plant extracts’ potential due to their medicinal properties and milder side effects.ObjectiveThis study conducts a systematic review and network meta-analysis (NMA) to assess the therapeutic effects of plant extracts on patients with heart failure, providing robust evidence for clinical practice.Materials and methodsA comprehensive search of databases, including PubMed, Embase, and Cochrane Library, was performed. Studies were screened using predefined criteria to extract data and assess quality. Network meta-analysis enabled direct/indirect comparisons of multiple plant extracts’ efficacy in heart failure intervention.ResultsA total of 20 studies encompassing 2,077 patients were incorporated into the analysis. Astragalus extract demonstrated the highest efficacy in enhancing the 6-min walk test (6-MWT) score (surface under the cumulative ranking curve [SUCRA]: 90.70%) and reducing tumor necrosis factor-alpha (TNF-α) levels (SUCRA: 74.4%). Shenfu extract exhibited superior efficacy in decreasing B-type natriuretic peptide (BNP) values (SUCRA: 68.2%) and enhancing the quality of life (QL) (SUCRA: 77.0%). Red ginseng extract was more effective in improving left ventricular ejection fraction (LVEF) (SUCRA: 77.9%), while Ginkgo biloba extract showed greater efficacy in ameliorating New York Heart Association (NYHA) functional classification (SUCRA: 76.5%). Despite these findings, heterogeneity and methodological issues in the studies warrant further high-quality, large-scale randomized controlled trials (RCTs) to validate the results and determine the optimal plant extract use in heart failure treatment.ConclusionAstragalus extract, red ginseng extract, Ginkgo biloba extract, Terminalia arjuna extract, and Shenfu extract have demonstrated significant efficacy in heart failure management in the study for the selection of optimal plant extracts based on enhanced indicators of cardiac function outcomes. Continued research through rigorous randomized controlled trials is essential to substantiate and refine the current evidence.